Psychosocial Strength Enhancing Resilience in Adolescents and Young Adults With Cancer. (January 2016) - Ishibashi, Akiko; Okamura, Jun; Ueda, Reiko; Sunami, Shosuke; Kobayashi, Ryoji; Ogawa, Junko
The purpose of this study was to explore ways of enhancing psychosocial strengths in newly diagnosed and relapsed adolescents and young adults (AYAs) to improve their resilience. A descriptive case study was used. The adolescent resilience model (ARM) and the self-sustaining process model were applied as theories. The data were analyzed using pattern-matching logic. Semistructured interviews were conducted with 18 patients aged 12 to 24 years and discharged within 10 years. We found that the newly diagnosed and the relapsing AYAs developed the 5 strength factors of the ARM during and after treatment. Whether the individuals cultivated a positive attitude and sense of purpose early or late, the AYAs developed resilience eventually. A positive attitude and sense of purpose during the early phase of care may be essential for improving resilience. The AYAs benefited from the support of their parents, friends, and previous experience. Individualized support and social resources may be important to develop these strengths. Further research is needed to develop strengths and improve resilience in newly diagnosed AYAs.